MATHEMATICAL IDENTIFICATION OF THE MECHATRONIC COMPLEX FOR THE CONSTRUCTION OF MINI TUNNELS IN URBAN CONDITIONS - Bulgakov, Alexey Grigoryevich; Vakolyuk, Alexander; Glebov, Nikolay; Otto, Jens (Journal of Applied Engineering Science, 2018)
This article is devoted to the development and investigation of the mathematical model of the mechatronic tunnel complex. The method for remote determination of the spatial position of the mini shield in the basic coordinate system is developed. The principle of constructing a laser system for determining the spatial coordinates of the tunnelling shield is offered. The exchange of information between the operator's console and the control equipment of the shield is shown.